Error analysis in the written English spelling of form four students in Sekolah Berasrama Penuh Integrasi, Gombak, Kuala Lumpur - Nor Farida bt. Ahmad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
The title of this thesis is “Error analysis in the written English of Form Four students in Sekolah Berasrama Penuh Integrasi Gombak, Kuala Lumpur”. The subject area being researched was confined to identify and analyze the errors done by Form Four students in a secondary school in Gombak Kuala Lumpur. The methodology used was, 62 Form Four students were instructed to write essays. Each essay was read thoroughly. The errors were identified and categorized according to classification recommended by Adam (1988) who had categorized them according to causes of misspelling – phonological as well as other non-phonological factors. There were eight classifications: phonemic conflations, homophones, suffixes, other consonantal omissions and insertions, glides, syllable structure (stressed vowel omissions and unstressed vowels), double consonant graphemes and silent <e>. 199 misspellings of were identified in guided essays while in continuous or free writing essays, the number of misspelled words was 234. In terms of percentage, the frequency of misspellings in the guided essays was 0.81% while in the continuous essay it was 0.88%. The frequency counts for misspelling identified are phonemic conflations 9.44%, homophones 7.08%, suffixes 13.4%, other consonantal omissions and insertions 9.71%, glides 9.97%, syllable structure 17.06%, double consonant consonant grapheme 16.7%, silent <e> 2.8%, one-two word confusion 6.8% and Bahasa Melayu spelling 6.8%. This study shows that misspelling due to suffixes is due to morphological (grammar) as well as phonological factors. There are also a lot of examples where pronunciation is the cause of misspelling. This study has found that misspellings arise because of pronunciation or intra lingual effect. Misspelling due to morphological reasons in the category of suffixes has been quite substantial.